2016
DOI: 10.2131/jts.41.sp27
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity between perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA)

Abstract: -Perfluoroalkyl substances (PFASs) are persistent environmental contaminants. Perfluorooctane sulfonate (PFOS) and Perfluorooctanoic acid (PFOA) are representatives of PFASs. Recently, the U.S. Environmental Protection Agency (US EPA) set the health advisory level as 70 parts per trillion for lifetime exposure to PFOS and PFOA from drinking water, based on the EPA's 2016 Health Effects Support Documents. Then, a monograph on PFOA was made available online by the International Agency for Research on Cancer, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 47 publications
0
53
0
1
Order By: Relevance
“…We recently reported that PFOS promotes MCF-10A proliferation by altering important regulatory cell cycle proteins and accelerating the cell cycle (Pierozan and Karlsson 2018 ). Despite the structural and many functional similarities, PFOS and PFOA have different toxicological effects (Tsuda 2016 ). Corroborating with this, the present study revealed that PFOA induces proliferation and acceleration of cell cycle by affecting different regulatory cell cycle proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that PFOS promotes MCF-10A proliferation by altering important regulatory cell cycle proteins and accelerating the cell cycle (Pierozan and Karlsson 2018 ). Despite the structural and many functional similarities, PFOS and PFOA have different toxicological effects (Tsuda 2016 ). Corroborating with this, the present study revealed that PFOA induces proliferation and acceleration of cell cycle by affecting different regulatory cell cycle proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al (2016) reported that C6A as well as C8A induced DNA damage in an alkaline comet assay, using TK +/-heterozygote of the TK6 human lymphoblastoid cell line. The possibility of C8A-induced DNA damage secondary to oxidative stress by the activation of PPARα to develop into human cancer was suggested when the C8A does not induce apoptosis properly (Tsuda, 2016). Further studies of C6A in relation to human toxicity may be necessary.…”
Section: Comparison To Human Datamentioning
confidence: 99%
“…Additionally, perfluorooctane sulfonate (PFOS) can promote MCF-10A breast epithelial cell proliferation by regulating cell cycle proteins and accelerating the cell cycle process (26). Although PFOS and PFOA are per-and polyfluoroalkyl substances which share structural and functional properties, they have different toxicological effects (27). The experiments performed in the present study demonstrated that PFOA promoted RD cell proliferation by regulating different cell cycle-related proteins.…”
Section: Discussionmentioning
confidence: 64%